2014
DOI: 10.1007/s10886-014-0530-1
|View full text |Cite
|
Sign up to set email alerts
|

Aspen Defense Chemicals Influence Midgut Bacterial Community Composition of Gypsy Moth

Abstract: Microbial symbionts are becoming increasingly recognized as mediators of many aspects of plant - herbivore interactions. However, the influence of plant chemical defenses on gut associates of insect herbivores is less well understood. We used gypsy moth (Lymantria dispar L.), and differing trembling aspen (Populus tremuloides Michx.) genotypes that vary in chemical defenses, to assess the influence of foliar chemistry on bacterial communities of larval midguts. We evaluated the bacterial community composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…This suggests that high concentrations of α-pinene are capable of altering the community structure of D. valens gut microbiota within a short time period (6 h). Similar results have shown that plant defensive chemicals influence herbivore insect gut microbiota in other systems, e.g., aspen defense chemicals were reported to influence the midgut bacterial community composition of Lymantria dispar L. [19,40], and the gut microbial community structures of Neotoma bryanti and Neotoma lepida were altered by plant secondary metabolites [41]. …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This suggests that high concentrations of α-pinene are capable of altering the community structure of D. valens gut microbiota within a short time period (6 h). Similar results have shown that plant defensive chemicals influence herbivore insect gut microbiota in other systems, e.g., aspen defense chemicals were reported to influence the midgut bacterial community composition of Lymantria dispar L. [19,40], and the gut microbial community structures of Neotoma bryanti and Neotoma lepida were altered by plant secondary metabolites [41]. …”
Section: Discussionmentioning
confidence: 54%
“…In addition to degrading plant compounds that would supplement missing nutrients [13], these microbial symbionts are capable of tolerating and detoxifying defensive chemicals of host plants [9,14,15]. On the contrary, the defensive chemicals of host plants along with decreased nutrition adversely affect insects’ growth and development [16], which can influence herbivore’s gut microbial community compositions when herbivores feed on plant tissues [17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Most non-entomopathogenic bacteria ingested by herbivorous insects are likely to be killed in the gut by alkaline pH, digestive enzymes, redox potential and the ionic strength of the midgut (Vallet-Gely et al, 2008). However, it is also becoming clear that phyllosphere bacteria can colonise and persist in insect midguts (Tang et al, 2012; and community composition in the gut can vary with plant species and genotype (Broderick et al, 2004;Mason et al, 2015). It has been suggested that microbiota ingested with foliage help to degrade defensive phytochemicals .…”
Section: Introductionmentioning
confidence: 99%
“…Related to resilience, similarities found between larvae feeding on 9.0 mg/ml of sinigrin and the control diet may be attributed to the host's physiological response or a direct effect of higher concentrations of glucosinolates on the microbiota in order to return the microbial community to its core structure [20]. In the study by Mason et al [20], differences in gypsy moth gut microbiota structure was influenced by various concentrations of tannins and phenolic glycosides (secondary plant compounds in trembling aspen genotypes). The study suggested that shifts in the microbial community could be attributed to either direct or indirect factors.…”
Section: Discussionmentioning
confidence: 99%
“…The natural host plants for P. rapae include important crop plants from the Brassicaceae family, all containing different types and concentrations of glucosinolates [19]. Recently it has been suggested that phytochemicals influence the midgut microbiota with the observation of foliar defense chemistry in trembling aspen tree genotypes being positively correlated with shifts in the gypsy moth midgut microbiota [20]. As with most plants, secondary chemical compounds act as a deterrent to herbivorous predators by releasing toxic derivatives after the degradation of the phytochemical [21].…”
Section: Introductionmentioning
confidence: 99%